Exploring perceived tension as a response to psychosocial work stress - Holte, Kari Anne; Vasseljen, Ottar; Westgaard, Rolf H. (Scandinavian Journal of Work, Environment & Health, 2003)
' ' OBJECTIVES ': 'This study extends the concept of tension, in part by observing changes in tension during the workday, to identify episodes causing elevated tension and relate them to bodily responses. ' ' METHODS ': 'Both questionnaires and qualitative interviews were used to describe the tension concept. Tension was scored on a visual analogue scale (VAS) every hour, and trapezius muscle activity and heart rate were recorded. Ninety-four female workers from four service occupations participated. ' ' RESULTS ': 'Tension was described as a musculoskeletal activation response involving the upper body regions, but also autonomic activation responses were described. The cause of elevated tension comprised a variety of situational demands; however, contact with other people causing negative emotions was a common factor. Averaged muscular activity and heart rate responses did not correlate with prolonged perceived tension, but the differential tension score between high- and low-tension periods correlated with the corresponding differential trapezius activity responses. The regression line indicated no effect of short-term variation in perceived tension on median muscle activity for differential VAS scores of 2 cm or less. An increase of 2% of maximal electromyographic activity for a differential VAS score of 4-5 cm was indicated. ' ' CONCLUSIONS ': 'This study identifies work exposures that cause tension, and it demonstrates a physiological correlate with the subjective perception of tension in the short term. The low recorded muscle activation response does not represent a risk factor for pain by the traditional standards used for recording and evaluating muscle activity responses, but it may point to underlying pain-inducing mechanisms, such as low-threshold overexertion of motor units.
Keywords: electromyography; perceived tension; psychosocial factor; psychosocial work stress; service occupation; stress; trapezius